Macrophage Inflammatory Protein-1 Alpha, a Potential Biomarker for Predicting Left Atrial Remodeling in Patients With Atrial Fibrillation - Chen, Yung-Lung; Wang, Hui-Ting; Lin, Pei-Ting; Chuang, Jiin-Haur; Yang, Ming-Yu (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Left atrial (LA) remodeling itself is an independent risk factor for ischemic stroke and mortality, with or without atrial fibrillation (AF). Macrophage inflammatory protein-1 alpha (MIP-1α) has been reported to be involved in the induction of autoimmune myocarditis and dilated cardiomyopathy. Little is known about whether MIP-1α can be used to predict LA remodeling, especially in patients with AF. Methods: We prospectively enrolled 78 patients who had received a cardiac implantable electronic device due to sick sinus syndrome in order to define AF accurately. AF was diagnosed clinically before enrollment, according to 12-lead electrocardiography (ECG) and 24-hour Holter test in 54 (69%) patients. The serum cytokine levels and the mRNA expression levels of peripheral blood leukocytes were checked and echocardiographic study was performed on the same day within one week after the patients were enrolled into the study. The 12-lead ECG and 24-hour Holter test were performed on the same day of the patients' enrollment, and the device interrogation was performed every 3 months after enrollment. The enrolled patients were clinically followed up for one year. Results: There was no difference in baseline characteristics, cytokine levels and mRNA expression between patients with and without AF. Larger LA volume was positively correlated with higher levels of MIP-1α (r= 0.461397, p= <0.0013) and interleukin 1 beta (r= 0.367, p= 0.006) and the atrial high-rate episodes (AHREs) burden (r= 0.59357, p< 0.001), and negatively correlated with higher levels of transforming growth factor (TGF)-1 (r= -0.271, p= 0.047) and TGF-3 (r= -0.279, p= 0.041). The higher AHREs burden and MIP-1 level could predict LA volume independently. The mRNA expression of RORC was negatively associated with the MIP-1 level. Conclusions: This study showed that higher MIP-1 was significantly associated with LA remodeling and may have the potentials to could independently predict LA remodeling in terms of a larger LA volume, and that circadian gene derangement might affect the expression of MIP-1.